Radiographic Assessment of First Tarsometatarsal Joint Shape and Orientation. (December 2019) - Koury, Kimberly; Staggers, Jackson R.; Pinto, Martim C.; Godoy-Santos, Alexandre L.; Smyth, Niall A.; Shah, Ashish B.; de Cesar Netto, Cesar
Background: Hypermobility within the first tarsometatarsal (TMT) joint is a predisposing factor for hallux valgus. The purpose of this study was to assess whether the shape and angulation of the first TMT joint are affected by the positioning of the foot in radiographs. Methods: Ten adult above-knee fresh-frozen cadaveric specimens were placed into a radiolucent apparatus that allowed controlled angulation of each foot at 0, 5, 10, 15, and 20 degrees in dorsiflexion, plantarflexion, inversion, and eversion. For each specimen, the first TMT joint angle (1TMTJA), shape of the distal articular surface of the medial cuneiform (flat or curved), and image quality of the first TMT joint were measured. Results: The mean value for 1TMTJA was 22.9 degrees (95% confidence interval [CI] 21.9-24). Individual anatomical variations of the specimens as well as the different angulations due to foot positioning significantly influenced the 1TMTJA (both P < .001). Joints that were found to have a flat configuration showed significantly increased 1TMTJA on average when compared to the ones with curved articular surface, 25.9 (95% CI 24.4-27.4) and 20.8 degrees (95% CI 19.5-22.0) ( P < .001), respectively. Image quality for visualization of the first TMT joint was progressively better for increased angles of dorsiflexion and inversion. Conclusion: The shape and angulation of the first TMT joint on radiographic evaluation are affected by the positioning of the foot. Clinical Relevance: Clinical usefulness of these radiographic characteristics is limited and should not influence operative planning in patients with possible instability of the first TMT joint.